The Role of Internal Audit in the Implementation of Good Governance in Islamic Banking - Yuli Dwi Yusrani Anugrah; Hamidah Wafi Masruro (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
Banking is a financial institution in which there are various kinds of services. The most influential thing in the service sector is trust. Apart from that, the good operation of a bank is also an added value for customers. This research uses qualitative research.